Clinical handbook of couple therapy - Jacobson, Neil S.; Gurman, Alan S. (Guilford, 1995)
Therapy with couples: A coming of age / Alan S. Gurman and Neil S. Jacobson Part I: Models of intervention with couples Section A: Major theories of couple therapy * Bowen family systems and marriage / Daniel V. Papero * Integrative behavioral couple therapy / Andrew Christensen, Neil S. Jacobson and Julia C. Babcock * Cognitive aspects of cognitive-behavioral marital therapy / Donald H. Baucom, Norman Epstein and Lynn A. Rankin * The ego-analytic approach to couple therapy / Daniel B. Wile * The emotionally focused approach to problems in adult attachment / Susan M. Johnson and Leslie S. Greenberg * Problem- and solution-focused couple therapies: The MRI and Milwaukee models / Varda Shoham, Michael Rohrbaugh and JoEllen Patterson * Psychoanalytic marital therapy / Jill Savege Scharff Section B: Group methods * Group therapy with couples / Judith Coche * Preventive intervention and relationship enhancement / Frank J. Floyd, Howard J. Markman, Shalonda Kelly, Susan L. Blumberg and Scott M. Stanley Part II: Couple therapy and relationally defined problems and issues Section A: Issues of culture, gender, and sexual orientation * Cross-cultural marriages / Celia Jaes Falicov * Redefining the past, present, and future: Therapy with long-term marriages at midlife / Carol M. Anderson, Sona A. Dimidjian and Apryl Miller * Gendered aspects of marital therapy / Cheryl Rampage * Therapy with same-sex couples: An introduction / Laura S. Brown Section B: Ruptures of the relational bond * Crises of infidelity / Frank S. Pittman III and Tina Pittman Wagers * The assessment and treatment of marital violence: An introduction for the marital therapist / Amy Holtzworth-Munroe, Stacia Beak Beatty and Kimberly Anglin * Facilitating healthy divorce processes: Therapy and mediation approaches / Froma Walsh, Lynn Jacob and Virginia Simons Part III: Couple therapy and common psychiatric disorders * Marital therapy in the treatment of alcohol problems / Barbara S. McCrady and Elizabeth E. Epstein * Anxiety disorders: The role of marital therapy / Michelle G. Craske and Lori A. Zoellner * A marital/family discord model of depression: Implications of therapeutic intervention / Ian H. Gotlib and Steven R. H. Beach * Conceptualization and treatment of eating disorders in couples / Maria P. P. Root * Object relations marital therapy of personality disorders / Samuel Slipp * Treating sexual desire disorders in couples / Julia R. Heiman, Pamela Hill Epps and Beatrice Ellis